2014
DOI: 10.4172/2155-9600.1000272
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Fetal Macrosomia at the Specialized Hospital of Gynecology and Obstetrics of Sidi Bel Abbes (West Of Algeria)

Abstract: Introduction: Fetal macrosomia is generally defined as a birth weight greater than 4000 grams and it is related to some adverse neonatal outcomes and maternal complications. The aim of our work is to identify the clinical profile of mothers who give birth to a macrosomic infant, and to study the maternal complications associated with delivering infants with a birthweight of 4000 grams or greater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…more than 35 years old, delivered more macrosomic babies than those mothers who were below 35 years old. This nding is consistent with several previous studies (19,(23)(24)(25)(26). Similarly, Said et.al and Kenny et.al (21,27), reported that the risk of high birth weight increased signi cantly with advancing maternal age (27).This may be due to the fact that with increasing the age of a mother, there exists the effect on metabolism, thereby accelerating the velocity of growth in the baby.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…more than 35 years old, delivered more macrosomic babies than those mothers who were below 35 years old. This nding is consistent with several previous studies (19,(23)(24)(25)(26). Similarly, Said et.al and Kenny et.al (21,27), reported that the risk of high birth weight increased signi cantly with advancing maternal age (27).This may be due to the fact that with increasing the age of a mother, there exists the effect on metabolism, thereby accelerating the velocity of growth in the baby.…”
Section: Discussionsupporting
confidence: 94%
“…Our analysis shows that mothers who had overweight/obesity BMI has greater chance to get high birth weight. This is analogous to many previous studies (22)(23)(24)(25)(26)34).…”
Section: Discussionsupporting
confidence: 91%
“…The average age of the patients was 28.9 years. [24]. On the other hand, endometriosis represented 13.93% compared to (5.95%), from Bukar to Niger in 2011 in 2011 [22].…”
Section: Discussion and Commentsmentioning
confidence: 95%
“…In Europe, on the other hand, the frequency of macrosomia is almost homogeneous around 5% despite small variations in some countries: 4.5% in France and 4.7% in Italy [11]. In Africa, although this prevalence varies with the socioeconomic level and other definition criteria according to each country [12][13][14]. In Mali, we have not recent data on this subject.…”
Section: Introductionmentioning
confidence: 96%